The Effectiveness of Emotion-Focused Therapy on Relational Ethics and Behavioral Emotion Regulation in Women with Marital Conflicts - Rezaei, Sara; Kohansal, Laleh; Bahri, Mahsa; Mansouri, Mounes; Yousofi, Maryam (Psychology of Woman Journal, 2025)
Objective: This study aimed to examine the effectiveness of Emotion-Focused Therapy (EFT) on relational ethics and behavioral emotion regulation in women experiencing marital conflicts.Methods and Materials: A randomized controlled trial design was employed with a total of 30 women from Tehran, who were randomly assigned to the experimental (n = 15) and control (n = 15) groups. The intervention consisted of eight 90-minute EFT sessions conducted over eight weeks, followed by a three-month follow-up assessment. The Behavioral Emotion Regulation Questionnaire (BERQ) and the Relational Ethics Scale (RES) were used to assess the dependent variables at pre-test, post-test, and follow-up stages. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests to evaluate within-group and between-group differences across time. Statistical analyses were conducted using SPSS-27 software.Findings: The results of repeated measures ANOVA indicated a significant main effect of time for relational ethics, F(2,27) = 30.64, p = 0.001, η² = 0.68, and behavioral emotion regulation, F(2,27) = 42.79, p = 0.001, η² = 0.72, demonstrating significant improvements over time in the experimental group compared to the control group. Bonferroni post-hoc analysis revealed significant differences between pre-test and post-test (p = 0.001) and pre-test and follow-up (p = 0.003) for both variables, while post-test to follow-up differences were not statistically significant.Conclusion: The findings suggest that Emotion-Focused Therapy is an effective intervention for improving relational ethics and behavioral emotion regulation in women with marital conflicts. The results indicate sustained positive effects over time, highlighting the potential of EFT as a valuable therapeutic approach in addressing marital distress and promoting emotional well-being.